Differences in cigarette smoking quit attempts and cessation between adults who did and did not take up nicotine vaping: Findings from the ITC four country smoking and vaping surveys. (September 2022) - Gravely, Shannon; Meng, Gang; Hammond, David; Hyland, Andrew; Michael Cummings, K.; Borland, Ron; Kasza, Karin A.; Yong, Hua-Hie; Thompson, Mary E.; Quah, Anne C.K.; Ouimet, Janine; Martin, Nadia; et al.
Highlights: There is mixed evidence whether nicotine vaping products (NVPs) can help adults quit smoking. Some evidence suggests that more frequent vaping is associated with increased abstinence from smoking. We found that compared to daily smokers who did not initiate vaping, daily vaping was associated with a greater likelihood of quitting smoking. Non-daily vaping was not associated with quit attempts or quit success compared to those who did not initiate vaping. These findings demonstrate that complete cigarette substitution may be more likely achieved when daily smokers use NVPs daily. Abstract: Introduction: There is mixed evidence as to whether nicotine vaping products (NVPs) can help adults who smoke transition away from cigarettes. This study investigated if self-reported attempts to quit smoking and smoking cessation, over a period of either 18 or 24 months, differed between respondents who initiated nicotine vaping versus those who did not. Outcome comparisons were made between those who: (1) initiated vaping vs. those who did not; (2) initiated daily or non-daily vaping vs. those who did not; and (3) initiated daily or non-daily vaping between surveys and continued to vape at follow-up (daily or non-daily) vs. those who did not initiate vaping. Methods: This cohort study included 3516 respondents from the ITC Four Country Smoking and Vaping Surveys (Australia, Canada, England, United Sates), recruited at Wave 1 (2016) or 2 (2018) and followed up at Wave 2 (18 months) and/or 3 (2020, 24 months). Adults who smoked daily at baseline and did not have a history of regular vaping were included. Initiation of vaping was defined as beginning to vape at least monthly between surveys. Respondents indicated whether they made an attempt to quit smoking between surveys. Smoking cessation was defined as those who self-reported no longer smoking cigarettes at follow-up. Results: Relative to those who did not initiate vaping, initiation of any daily vaping between surveys was associated with a greater likelihood of smokers making a cigarette quit attempt (p < 0.001) and quitting smoking (p < 0.001). Among smokers who attempted to quit smoking, initiation of daily vaping was associated with a greater likelihood of being abstinent from smoking at follow-up (p = 0.001). Respondents who initiated vaping between surveys and were vaping daily at follow up were significantly more likely to have attempted to quit smoking (p < 0.001) and to have quit smoking (p < 0.001) than those who did not initiate vaping. Respondents who initiated non-daily vaping did not differ significantly from those who did not initiate vaping on any of the outcome measures. Conclusions: Daily NVP use was associated with increased attempts to quit smoking and abstinence from smoking cigarettes. These findings are consistent with the concept that complete cigarette substitution may be more likely to be achieved when smokers vape nicotine daily.